The Effect of Katsu Training on The Efficiency of Some Physical and Physiological Variables and Its Impact on The Level of Some Offensive Skills of Young Taekwondo Players - Mahmoud, Khalid (Indonesian Journal Publisher, 2025)
The research aims to identify the effect of katsu training on the efficiency of some physical and physiological variables and its impact on the level of some offensive skills of young taekwondo players by determining. Because of its suitability for the nature of the research, the researcher used the experimental design with two measurements before and after one experimental group, and the researcher selected a random sample of (24) players registered in the Iraqi Taekwondo Federation from the youth category, and one of the most important results was that the Katsyu training caused a development in the physical, physiological and skill abilities of young Taekwondo players, and the most important recommendations were that Katsyu training should be used to develop the physical, physiological and skill abilities of Taekwondo players.